Serine proteases and protease-activated receptor 2 mediate the proinflammatory and algesic actions of diverse stimulants - Cattaruzza, F (Blackwell Publishing Ltd, 2014)
BACKGROUND AND PURPOSE: Although serine proteases and agonists of protease-activated receptor 2 (PAR2) cause inflammation and pain, the spectrum of proteases that are activated by proinflammatory and algesic stimuli and their contribution to inflammatory pain are uncertain. EXPERIMENTAL APPROACH: Enzymic assays and selective inhibitors were used to characterize protease activity in mice after intraplantar injections of formalin, bradykinin, PAR2 activating peptide (AP) or vehicle. The capacity of these proteases and of recombinant mouse trypsin 4 to cleave fragments of PAR2 and to activate PAR2 in cell lines was determined. Protease inhibitors and par(2)(−/−) mice were used to assess the contributions of proteases and PAR2 to pain and inflammation. KEY RESULTS: Intraplantar injection of formalin, bradykinin or PAR2-AP led to the activation of proteases that were susceptible to the serine protease inhibitor melagatran but resistant to soybean trypsin inhibitor (SBTI). Melagatran inhibited mouse trypsin 4, which degraded SBTI. Proteases generated in inflamed tissues cleaved PAR2-derived peptides. These proteases and trypsin 4 increased [Ca(2+)](i) in PAR2-transfected but not in untransfected cells, and melagatran suppressed this activity. Melagatran or PAR2 deletion suppressed oedema and mechanical hypersensitivity induced by intraplantar formalin, bradykinin and PAR2-AP, but had no effect on capsaicin-induced pain. CONCLUSIONS AND IMPLICATIONS: Diverse proinflammatory and algesic agents activate melagatran-sensitive serine proteases that cause inflammation and pain by a PAR2-mediated mechanism. By inducing self-activating proteases, PAR2 amplifies and sustains inflammation and pain. Serine protease inhibitors can attenuate the inflammatory and algesic effects of diverse stimuli, representing a useful therapeutic strategy.